Psychiatric disorders and young adult milestones in HIV-exposed, uninfected youth. Issue 4 (2nd April 2020) - Bucek, Amelia; Mellins, Claude Ann; Leu, Cheng-Shiun; Dolezal, Curtis; Korich, Rehema; Wiznia, Andrew; Abrams, Elaine J.
ABSTRACT: The global population of perinatally HIV-exposed but uninfected (HEU) children is growing, with relatively little known about their psychosocial outcomes, particularly across adolescence and young adulthood. Using data from a longitudinal cohort study of HEU youth in New York City ( N  = 134), we examine rates of substance use disorders (SUD) and non-SUD psychiatric disorders (mood, anxiety, and behavioral) at five time-points during adolescence and young adulthood, as well as associated demographic and environmental factors and the association of ever having a disorder with young adult developmental milestones. HEU participants in this study experienced high rates of psychiatric disorders, particularly SUD in young adulthood. During the entire study period (2003–2018), over one third were diagnosed at least once with a SUD, and 69% were diagnosed with a non-SUD psychiatric disorder. Older age and female gender were associated with higher rates of non-SUD diagnoses. A history of meeting criteria for any disorder at any time point was associated with reduced odds in young adulthood of working or being in school and increased odds of reporting incarceration, homelessness, and recent condomless sex. There is an urgent need to develop systems to follow HEU youth and provide services to intervene and treat psychiatric disorders, including substance use.